The effect of the COVID-19 pandemic on immigration and immigrant wellbeing in the United States - Krannich, Sascha; Massey, Douglas S.; Justus Liebig University Giessen (My University, 2024)
This article highlights the effect of the COVID-19 pandemic on immigration and immigrant wellbeing in the United States by focusing on all categories of migrants, documented and undocumented. We argue that in the wake of the pandemic, immigrants disproportionately experienced higher rates of unemployment, greater losses of income, more exposure occupational risks, and higher rates of food and housing insecurity, all of which exacerbated preexisting differentials in access to health and health care to generate higher rates of COVID infection, morbidity, and mortality among adults and stunted educational outcomes for their children. The prospects for a full post-pandemic recovery of immigrants' wellbeing are dampened by the severe nature of COVID's negative effects on immigrants; the unusually hostile context of reception immigrants face after the pandemic; the large number of immigrants lacking legal status or holding tenuous documentation; and the formidable deportation regime that prevails in the United States that puts a great strain on immigrant communities. Undocumented migration has surged to restart undocumented population growth, further clouding the future for immigrants in the country. It is unclear whether reforms proposed by the Biden Administration be enacted and successful in improving their prospects. In general, this article aims to contribute to the broader discussion about migration and health policies.
Keywords: ddc:900